KELUARGA: SEBAGAI SUMBER BELAJAR PADA PENDIDIKAN ANAK USIA DINI (Suatu Tinjauan Menurut Teori Sosial Kognitif Bandura) - Nelva Rolina (MAJALAH ILMIAH PEMBELAJARAN, 2006)
Family is a smallest unit than society unit. Family, especially parents can be an effective learning resource by utilization in instructional process for children at home. They can be the model which is imitated by children. With social cognitive theory from Bandura which is had an observational learning theory, family who’s be model can educate and bring up the children with their characteristics.Instructional process which is given at home by family must be synchronous with school experience and school lesson, especially moral. Example, children is touch about ABCD in the school, but they are touch about EFGH at home. It’s not good for children. So, it must be an effective communication between family (parents) and teacher at school.Family is model for children. And then, they must show interest in a children problem and have a certain attitude. Children will imitate anything which is done by people around them. So, family (parents) who’s be model should give a good atmosphere learning for children, and should give good lesson and good experience for children.